Failure analysis and prevention - Becker, William T.; Shipley, Roch J. (ASM Handbook ;, 2002)
"Volume 11 describes the principles, practices, and analytical techniques of failure analysis. It provides information on life assessment and manufacturing operations, examining the causes, mechanisms, and appearances of common failure modes, including fracture, corrosion, wear, and distortion. It also discusses general engineering considerations associated with failure prevention, covering fundamental root causes, materials selection, and the role of design reviews in prevention and analysis."--